Validation of clinical risk scores for laparoscopic liver resections of colorectal liver metastases: A 10‐year observed follow‐up study. Issue 6 (29th July 2016) - Barkhatov, Leonid; Fretland, Åsmund A.; Kazaryan, Airazat M.; Røsok, Bård I.; Brudvik, Kristoffer W.; Waage, Anne; Bjørnbeth, Bjørn A.; Sahakyan, Mushegh A.; Edwin, Bjørn
Abstract : Objective: The aim of this study was to validate clinical risk scores in patients underwent laparoscopic resection of colorectal liver metastases (CLM) with 5 years follow‐up or more, and assess 5‐ and 10‐year actual survival in this group. Methods: A total of 516 laparoscopic liver resections were performed in 406 patients with CLM between February 1998 and September 2015. A follow‐up of 5 and 10 years could be assessed in 144 and 29 patients, respectively. The Fong score, pre‐ and postoperative Basingstoke Predictive Index (BPI), Nordlinger score, and Iwatsuki score were validated. Results: Five‐ and ten‐year cancer‐related actual survival was 54% and 32%, respectively. The Fong score, pre‐ and postoperative BPI and the Nordlinger score divided patients into risk groups with significant difference in survival between the groups. However, predicted 5‐year survival rates were lower than the actual 5‐year survival (mean difference in 17%, 13%, 20%, and 30%, respectively). Conclusion: The Fong score, pre‐ and postoperative BPI and the Nordlinger score systems can be used to predict survival for laparoscopically operated patients in the era of multimodal‐treatment after adjusting of survival rates. The actual five‐ and 10‐year survival after laparoscopic resection of CLM is similar to results previously published for open liver resection. J. Surg. Oncol. 2016;114:757–763 . © 2016 Wiley Periodicals, Inc.